1986
DOI: 10.1128/aac.29.3.535
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in susceptibility to quinolones of outer membrane mutants of Salmonella typhimurium and Escherichia coli

Abstract: The mechanism of penetration of quinolones through the bacterial outer membrane was studied with lipopolysaccharide-deficient and porin-deficient mutants. The data indicated that the lipopolysaccharide layer might form a permeability barrier for hydrophobic quinolones such as nalidixic acid but not for hydrophilic quinolones such as norfloxacin and ciprofloxacin. The results also showed that quinolones with a low relative hydrophobicity appeared to permeate through OmpF porin, whereas quinolones with a high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(148 citation statements)
references
References 24 publications
8
140
0
Order By: Relevance
“…The increased susceptibility of E. coli to nalidixic acid in 4% phosphate was not as obvious (a twofold reduction of the MIC), but could be seen by using the MS-2 Abbott Research System (data not shown). These data indicated that the hydrophobic antibiotic, nalidixic acid, may be able to penetrate bacteria by passing through the hydrophobic domain of the outer membrane, as was suggested in a study with an LPS-deficient mutant (13).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The increased susceptibility of E. coli to nalidixic acid in 4% phosphate was not as obvious (a twofold reduction of the MIC), but could be seen by using the MS-2 Abbott Research System (data not shown). These data indicated that the hydrophobic antibiotic, nalidixic acid, may be able to penetrate bacteria by passing through the hydrophobic domain of the outer membrane, as was suggested in a study with an LPS-deficient mutant (13).…”
Section: Discussionsupporting
confidence: 48%
“…The hope was to change E. coli surface properties (hydrophobicity and phospholipid content) to investigate a possible nonspecific lipophilic diffusion pathway for ceftazidime. Cephaloridine, a dipolar ionic ,-lactam that penetrates readily through the water-filled hydrophilic pores of the outer membrane of gram-negative bacteria (34), and the more hydrophobic antibiotic nalidixic acid, which may diffuse through the LPS-phospholipid bilayer in a nonspecific manner (a nonporin pathway) (13), served as controls in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the nfxB gene might be a novel gene in P. aeruginosa PAO; however, further genetic studies are in progress. We found previously that the outer membrane permeability to new quinolones such as norfloxacin in E. coli and Salmonella typhimurium differed from that to nalidixic acid (12). The incomplete cross-resistance among quinolones in E. coli is known (18,41), and this phenomenon was also observed in P. aeruginosa (32).…”
Section: Discussionmentioning
confidence: 97%
“…The uptake of norfloxacin by P. aeruginosa cells was measured by the method described previously (12,15). Bacterial cells were grown at 37°C in antibiotic medium 3 (Difco), and norfloxacin was added to the bacterial culture (A570 = 0.7) to a final concentration of 10 ,ug/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Ofloxacin is freely soluble in acetic acid, slightly soluble in water, methanol, ethanol or acetone. The octanol/water partition coefficient for ofloxacin was reported to be -0.48 [1,2] Ofloxacin which is the focus of this review is a second generation fluoroquinolone with a 6-fluoro substituent and a 7-piperazinyl substituent on the quinolone ring structure [11] Entrapped niosomes were prepared by hand shaking and ether injection process with different ratios of (1:1, 1:2 and 1:3) cholesterol and Span-80 (Non-ionic surfactant). The niosomes prepared were in the size of 0.5-2.5 microns in case of hand shaking process and 0.5-2.5 microns in case of Ether injection process.…”
Section: Related Workmentioning
confidence: 99%